If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-3p+8=-p
We move all terms to the left:
-3p+8-(-p)=0
We add all the numbers together, and all the variables
-3p-(-1p)+8=0
We get rid of parentheses
-3p+1p+8=0
We add all the numbers together, and all the variables
-2p+8=0
We move all terms containing p to the left, all other terms to the right
-2p=-8
p=-8/-2
p=+4
| 8+w=5 | | 3c+60=5-7c | | 2x+50+x-10+x=180 | | 3(x+1)/3=2x-5 | | 4x-13+2x=3+6x-15 | | 5(x-5)+1=-34 | | 4t=-5+3t | | -3−2n=-n | | 5/9x=3/7 | | 6(x+3)+5=35 | | 48=2u+4u | | R=2x+11/2 | | 0x+2=9x+3 | | -3s=8-4s | | 1+x=16x-32 | | 5(x-3)+1=-14 | | 28=13v-6v | | -8+n=-7n | | T(n)=n+T(2n-1) | | 4=q+1 | | 7x-3(x-1)=15 | | 2(x-1)+3(x-2)=4x-3 | | 2(6x-5)-8x=14 | | 3x+4∘+8x−28∘=108∘ | | 7x+54=-2 | | 4(3x-1)-9=11 | | 4x-12=31 | | 3x-7=-3x | | x+1/6=-3/5 | | 12a(24)=4 | | 35x+3=45+2x | | x/3+15=40 |